Penegasan Hak Anak Persepektif Islam - Husni, Muhammad (Fakultas Syariah - IAI Al-Qolam Malang, 2017)
The Law of the Republic of Indonesia number 35 of 2014 on the amendment of Law number 23 of 2002 concerning child protection provides the understanding of the child, ie someone who is not yet 18 years of age. While the rights and obligations of children as described in Article 4 of the Constitution of child protection are every child has the right to grow and develop and to participate fairly according to the dignity and dignity of humanity and to get protection from violence and discrimination. According to the positive law, rights and obligations of children have been reviewed and determined. The writing of this article examines the rights and obligations of the child's Islamic perspective. The author concludes that child protection can be done by fulfilling the rights of the child that includes the right to live, grow and develop; the right to worship, to think and to express; right to education; the right to express and hear his opinion; and the right to protection from violence and discrimination. The person responsible for the protection of the child is the parents, the school, the community and the state in the guidance of the child during the puberty of religious worship. Worship is a manifestation of faith. Without the existence of worship, it is not using any form of belief of a Muslim. Keywords: Children Act, Child Rights, Islamic Law